Modelling the impact of the tier system on SARS-CoV-2 transmission in the UK between the first and second national lockdowns. Issue 4 (22nd April 2021) - Laydon, Daniel J; Mishra, Swapnil; Hinsley, Wes R; Samartsidis, Pantelis; Flaxman, Seth; Gandy, Axel; Ferguson, Neil M; Bhatt, Samir
Abstract : Objective: To measure the effects of the tier system on the COVID-19 pandemic in the UK between the first and second national lockdowns, before the emergence of the B.1.1.7 variant of concern. Design: This is a modelling study combining estimates of real-time reproduction number Rt (derived from UK case, death and serological survey data) with publicly available data on regional non-pharmaceutical interventions. We fit a Bayesian hierarchical model with latent factors using these quantities to account for broader national trends in addition to subnational effects from tiers. Setting: The UK at lower tier local authority (LTLA) level. 310 LTLAs were included in the analysis. Primary and secondary outcome measures: Reduction in real-time reproduction number Rt . Results: Nationally, transmission increased between July and late September, regional differences notwithstanding. Immediately prior to the introduction of the tier system, Rt averaged 1.3 (0.9–1.6) across LTLAs, but declined to an average of 1.1 (0.86–1.42) 2 weeks later. Decline in transmission was not solely attributable to tiers. Tier 1 had negligible effects. Tiers 2 and 3, respectively, reduced transmission by 6% (5%–7%) and 23% (21%–25%). 288 LTLAs (93%) would have begun to suppress their epidemics if every LTLA had gone into tier 3 by the second national lockdown, whereas only 90 (29%) did so in reality. Conclusions: The relatively small effect sizes found in this analysis demonstrate that interventions at least as stringent as tier 3 are required to suppress transmission, especially considering more transmissible variants, at least until effective vaccination is widespread or much greater population immunity has amassed.